PELATIHAN DAN PENDAMPINGAN PENINGKATAN KAPASITAS PRODUKSI DAN PENJUALAN DI UMKM J&R DESA DUWET - Muhammad Akhlis Rizza; Evi Suwarni; Supa Kusuma Aji (Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to increase production and sales capacity in MSMEs J&R Duwet Village, Tumpang District, Malang Regency. J&R MSMEs are facing bottlenecks in the drying and sorting process of cassava chip dough, which leads to low production capacity. The solution offered is to make a drying device (oven) with a capacity of 100 kg/hour and a roll system dough filer. In addition, training was provided on packaging and marketing products with new logos to increase sales. The method used in this program is intensive training and mentoring. The result of this service has a significant impact on J&R MSMES. Increased production capacity from 50 kg/hour to 100 kg/hour after the use of new equipment, as well as improved product quality through a more consistent drying process. In addition, packaging and marketing training successfully increased the attractiveness of products in the local market and expanded the sales reach. With the new logo, J&R's MSME products are better known, and sales turnover increased by about 15% in the months following the implementation of the program.